1997
DOI: 10.1046/j.1460-9592.1997.d01-121.x
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy of an injectable prodrug of acetaminophen in children after orthopaedic surgery

Abstract: The analgesic efficacy and safety of propacetamol, an injectable prodrug of acetaminophen, (paracetamol) were studied in 87 children (36 boys, 51 girls; age 6-13; mean age 9.5 years) immediately after limb surgery. Using a double-blind, randomized, parallel group design, the effects of a single IV infusion of 30 mg.kg-1 propacetamol (i.e. 15 mg.kg-1 acetaminophen) were compared with a single injection of placebo (PL). Efficacy was assessed on pain scores rated on a four-point verbal scale, a five-point visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 0 publications
1
23
0
4
Order By: Relevance
“…17 In children, acetaminophen provided signifi cantly greater analgesic effect than placebo, after orthopedic surgery. 18 Aubrun et al 19 studied effects of ketoprofen after scoliosis surgery and observed reduced morphine requirements and better analgesia in adults who had received ketoprofen in addition to acetaminophen, compared with acetaminophen alone.…”
Section: Discussionmentioning
confidence: 99%
“…17 In children, acetaminophen provided signifi cantly greater analgesic effect than placebo, after orthopedic surgery. 18 Aubrun et al 19 studied effects of ketoprofen after scoliosis surgery and observed reduced morphine requirements and better analgesia in adults who had received ketoprofen in addition to acetaminophen, compared with acetaminophen alone.…”
Section: Discussionmentioning
confidence: 99%
“…Nach rascher Hydrolyse wird Paracetamol freigesetzt. Ein Gramm Propacetamol setzt dabei 0,5 g Paracetamol frei [36]. Es empfiehlt sich die Verabreichung mittels Kurzinfusion; eine kontinuierliche Verabreichung ist aufgrund der Instabilität der Lösung nicht möglich.…”
Section: Intravenöse Gabeunclassified
“…So wurde in einer Untersuchung zu Propacetamol bei Kindern der maximale antipyretische Effekt 2 h nach intravenöser Applikation beobachtet [35]. In einer anderen Untersuchung zeigte sich erst eine Stunde nach Applikation ein signifikanter Unterschied bezüglich der analgetischen Wirkung im Vergleich zu Placebo [36]. Genauere Angaben zu pharmakokinetischen Aspekten sind nicht möglich, da nur vereinzelte Studien zur Anwendung von Propacetamol bei Kindern vorliegen.…”
Section: Intravenöse Gabeunclassified
See 1 more Smart Citation
“…In this context, the use of intravenous acetaminophen is currently considered as the basic postoperative analgesic due to its low cost and an appropriate safety profile in the management of post-tonsillectomy pain (7). Furthermore, parenteral formulation of acetaminophen has been introduced for children and its pharmacological safety has been established among this age-subgroups (8, 9). …”
Section: Introductionmentioning
confidence: 99%